2020
DOI: 10.3390/agriculture10040126
|View full text |Cite
|
Sign up to set email alerts
|

Microbial β-glucan Incorporated into Muffins: Impact on Quality of the Batter and Baked Products

Abstract: Microorganisms can be a promising source of bioactive food ingredients derived from unconventional agricultural farms. The quality of batter and final products in which 20%–80% of the fat has been replaced by β-glucan, obtained from microorganisms, was analyzed. The instrumental texture measurements showed that β-glucan batter and muffins were harder than the control sample. Fat substitution over 40%, while enriching muffins with yeast β-glucan (over 2%), led to a decrease in the quality of products after baki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Also, other studies showed that the elimination of lipids from confectionery products is associated with a deterioration in quality [34]. Other authors also reported a negative impact (decrease in volume and height) of fat substitution by β-glucans of various origins on the physical quality of fatty sponge cake products [16,21,35]. This is because fat molecules are an important component of baked goods: they hold the air in raw dough, thereby increasing its volume and creating a structure in the final product [19,36].…”
Section: Nutritional Value Of Lipids In Shortbread Biscuits and Their...mentioning
confidence: 96%
See 1 more Smart Citation
“…Also, other studies showed that the elimination of lipids from confectionery products is associated with a deterioration in quality [34]. Other authors also reported a negative impact (decrease in volume and height) of fat substitution by β-glucans of various origins on the physical quality of fatty sponge cake products [16,21,35]. This is because fat molecules are an important component of baked goods: they hold the air in raw dough, thereby increasing its volume and creating a structure in the final product [19,36].…”
Section: Nutritional Value Of Lipids In Shortbread Biscuits and Their...mentioning
confidence: 96%
“…In addition, due to the negative impact of TFA on the body, the European Commission Regulation 2019/649 was in force since 2021, limiting the content of industrial TFA in fat (up to 2 g TFA/100 g of product) [13]. Therefore, it is advisable to replace industrial shortenings in processed food with ingredients with high biological potential, e.g., dietary fiber biomolecules [14][15][16][17][18]. It was reported that many fibers with a nutritional value could be used to substitute fat in bakery products, such as inulin, fruits, and vegetable fibers, cereal fiber, and β-glucans [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the exploitation of edible crops for this process challenges global food security. Furthermore, industrial β-glucan extraction is based predominantly on chemical methods (bases, acids, and solvents) and consequently, it could generate toxic and harmful residues [6][7][8]. Likewise, the extraction method selected can interfere with long extraction time, low yields, reduced purity, high process costs, and lower environmental sustainability [5].…”
Section: Introductionmentioning
confidence: 99%
“…Microbial β-glucan production is a potential alternative, with the main advantages including sustainability, a high degree of purity, prominent production efficiency, rapid microbial growth, and independence from seasonal factors [8]. Lasiodiplodan is a βglucan-type exopolysaccharide with great commercial potential considering its versatile biological functions such as antimicrobial, antioxidant, anticoagulant, protective activity against induced DNA damage by doxorubicin, hypoglycemic and transaminase activities, and other properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, they have high energy and sugar indicators and low nutritional value [5,6]. Muffins are prepared by the technology that involves a separate mixing of liquid and dry ingredients [7].…”
Section: Introductionmentioning
confidence: 99%